2017
DOI: 10.1016/j.biopha.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk of MicroRNA and hydrogen sulfide: A novel therapeutic approach for bone diseases

Abstract: Bone homeostasis requires a balance between the bone formation of osteoblasts and bone resorption of osteoclasts to maintain ideal bone mass and bone quality. An imbalance in bone remodeling processes results in bone metabolic disorders such as osteoporosis. Hydrogen sulfide (H2S), a gasotransmitter, has attracted the focus of many researchers due to its multiple physiological functions. It has been implicated in anti-inflammatory, vasodilatory, angiogenic, cytoprotective, anti-oxidative and anti-apoptotic mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 113 publications
1
16
0
Order By: Relevance
“…In other rodent models of lung pathology, endogenous H 2 S has been suggested to have a protective role of anti-inflammation and bronchodilation in chronic cigarette smoke-induced pulmonary injury in rats [ 49 ], and H 2 S provokes tachykinin-mediated neurogenic inflammation that is mediated by stimulation of TRPV1 receptors on the sensory nerve endings in Guinea Pigs [ 50 ]. Furthermore, considering the emergence of data suggesting a degree of cross-talk between H 2 S and epigenetic modifiers such as miRNAs [ 51 , 52 ], and our own data suggesting broadly different epigenetic profiles between lung pathologies (including COPD) in ASM [ 4 , 9 , 10 , 12 , 13 ]. Hence, the difference between a COPD ASM cell and a ‘healthy’ ASM cell may incorporate one, or more likely, more of these H2S targets/activators.…”
Section: Discussionmentioning
confidence: 98%
“…In other rodent models of lung pathology, endogenous H 2 S has been suggested to have a protective role of anti-inflammation and bronchodilation in chronic cigarette smoke-induced pulmonary injury in rats [ 49 ], and H 2 S provokes tachykinin-mediated neurogenic inflammation that is mediated by stimulation of TRPV1 receptors on the sensory nerve endings in Guinea Pigs [ 50 ]. Furthermore, considering the emergence of data suggesting a degree of cross-talk between H 2 S and epigenetic modifiers such as miRNAs [ 51 , 52 ], and our own data suggesting broadly different epigenetic profiles between lung pathologies (including COPD) in ASM [ 4 , 9 , 10 , 12 , 13 ]. Hence, the difference between a COPD ASM cell and a ‘healthy’ ASM cell may incorporate one, or more likely, more of these H2S targets/activators.…”
Section: Discussionmentioning
confidence: 98%
“…3C). To confirm these findings, the caspase-3 activity was also detected as a common marker for apoptosis (9,31). A consistent result further suggested that the overexpression of miR-497 induced apoptosis by markedly increasing the caspase-3 activity (~2.2 fold) (Fig.…”
Section: Overexpression Of Mir-497 Induces MM Apoptosis It Wassupporting
confidence: 65%
“…They are considered to function as mRNA regulators by interacting with the 3'-untranslated region (3'UTR) of the targeted mRNA transcript and leading to degradation (2)(3)(4)(5). Several, if not all, biological processes are reported to be regulated by miRNAs, including cell cycle, proliferation, metabolism, immune response, hematopoiesis and differentiation (6)(7)(8)(9)(10). It is widely accepted that miRNAs are vital in the process of tumorigenesis by targeting key factors (11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on physiological and pathophysiological roles of H 2 S, revealed its therapeutic potential in bone diseases (Liu et al, 2014 ; Zhai et al, 2017 ).…”
Section: Hydrogen Sulfide and Effects On Bonementioning
confidence: 99%